Effects of light intensity on the morphology and CAM photosynthesis of Vanilla planifolia Andrews (2017)
Vanilla planifolia is a neotropical orchid, whose fruits produce the natural vanilla, a fundamental ingredient for the food and cosmetic industry. Because of its importance in the world market, it is cultivated in many tropical countries and recently its cultivation has started in Colombia. This species requires shade for its development; however, the optimal of light conditions are unknown. This work evaluates the effect of different light intensities on CAM photosynthesis, physiology, morphology, and growth of this species. For this, vanilla seedlings were subjected to four treatments of relative illumination (RI) (T1=8%, T2=17%, T3=31% and T4=67%). Most CO2 assimilation occurred along night in all treatments, which confirms that vanilla is a strong CAM species. Plants grown under high lighting (67% RI) had almost half of the photosynthesis in treatments of intermediate lighting (17 and 31%), which is consistent with the lower nocturnal acid accumulation in that treatment. Likewise, the photochemical efficiency of photosystem II (Fv / Fm) showed that in plants of the 67% RI occurred high radiation stress. On the other hand, vanilla plants reached greater length, leaf area, and total biomass when grown under intermediate radiation (17 and 31% RI). These results suggest that high radiation alters the functioning of vanilla plants, inhibiting photosynthesis and growth, and that highly shaded environments not significantly affected the CAM photosynthesis of vanilla; however, in the long-term this species showed higher photosynthesis and growth under intermediate levels of radiation